SATISFAÇÃO DOS EXPOSITORES E VISITANTES DA TEC-E-INOVA 2007 - TIZOTTE, ALINE L.; RAMOS, FABRÍCIO; KUHN, IVO N.; SOARES, JÚLIO C. V.; ZAMBERLAN, LUCIANO; FROEMMING, LURDES M. S.; BARROS, RODRIGO D. (Salão do Conhecimento, 2013)
Resumo